Technical Perspective: Maintaining Quality in the Face of Distributed Development. - Herbsleb, James (Communications of the ACM, 2009)
The article discusses the article "Does Distributed Development Affect Software Quality? An Empirical Case Study of Windows Vista" by Christian Bird, Nachiappan Nagappan, Premkumar Devanbu, Harald Gall, and Brendan Murphy, published elsewhere in the same issue. It addresses the question of whether global software development affects software quality.